Clean Code in PHP Expert Tips and Best Practices to Write Beautiful, Human-Friendly, and Maintainable PHP - Windler, Carsten (Packt Publishing, Limited, 2022)
Practical lessons, examples, and practices from PHP experts on how to take your PHP skills to a professional level Key Features Easily navigate to key clean code principles specific to PHP development with this hands-on guide Learn the how and why of writing clean code through practical examples Skip the superfluous knowledge and grasp everything that's relevant to the real-world development environment Book Description PHP is a beginner-friendly language, but also one that is rife with complaints of bad code,;yet no clean code books are specific to PHP. Enter Clean Code in PHP. This book is a one-stop guide to learning the theory and best practices of clean code specific to real-world PHP app development environments. This PHP book is cleanly split to help you navigate through coding practices and theories to understand and adopt the nuances of the clean code paradigm. In addition to covering best practices, tooling for code quality, and PHP design patterns, this book also presents tips and techniques for working on large-scale PHP apps with a team and writing effective documentation for your PHP projects. By the end of this book, you'll be able to write human-friendly PHP code, which will fuel your PHP career growth and set you apart from the competition. What you will learn Build a solid foundation in clean coding to craft human-readable code Understand metrics to determine the quality of your code Get to grips with the basics of automated tests Implement continuous integration for your PHP applications Get an overview of software design patterns to help you write reusable code Gain an understanding of coding guidelines and practices for working in teams Who this book is for This book is for early-career PHP developers who wish to avoid writing messy code by learning how to write understandable and maintainable code that sets them apart from rest. The book assumes familiarity with PHP coding and principles, but no knowledge of advanced principles will be necessary.